A Study of Sexual Harassment of Women at Workplace Environment - Sanjeev Kumar; Ritika Sharma (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Today's culture has made sexual harassment both a hobby and a major issue. When women experience sexual harassment on the job, it compromises their fundamental rights to equality under articles 14 and 15 of India's Constitution, as well as her right to life and to live with dignity under article 21 of the Constitution, and her right to exercise and career or to hold on any occupation, exchange, or business with, which includes a right to a secure environment free from sexual harassment. We will use Vishaka and others as the point of origin of the sexual harassment. The case of V U.O.I. 1997 deals with the problem of sexual harassment of women in the workplace. It is a landmark judgment cases within side the records of sexual harassment which as being determined through preferred court. Sexual harassment is a hassle giving bad impact on each women and men is not unusual place everywhere. Every 2nd and each minute they're being stressed. Especially girls in India are taken into consideration as the second one grade citizens. They are violated, exploited and confused by and large at workplaces. Sexual harassment is a severe hassle within side the place of work. The look at analyzes the sexual harassment of girls in popular and in particular. The observe additionally complements the techniques for the safety of ladies from sexual harassment on the place of job.